2015
DOI: 10.1186/s12887-015-0470-0
|View full text |Cite
|
Sign up to set email alerts
|

“Why not bathe the baby today?”: A qualitative study of thermal care beliefs and practices in four African sites

Abstract: BackgroundRecommendations for care in the first week of a newborn’s life include thermal care practices such as drying and wrapping, skin to skin contact, immediate breastfeeding and delayed bathing. This paper examines beliefs and practices related to neonatal thermal care in three African countries.MethodsData were collected in the same way in each site and included 16–20 narrative interviews with recent mothers, eight observations of neonatal bathing, and in-depth interviews with 12–16 mothers, 9–12 grandmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 27 publications
3
45
1
3
Order By: Relevance
“…week (Joseph, et al, 2013). Whereas, bathing occurred soon after delivery in Nigerian, but was delayed for several hours or until the next day for most Tanzanian and Ethiopian narrative mothers (Adejuyigbe, et al, 2015). Present study also showed the ritual of massage which is consistent with finding of the study which also emphasized the practice of oil massage before bath by mothers (Joseph, et al, 2013).…”
Section: Hygiene Practicessupporting
confidence: 88%
“…week (Joseph, et al, 2013). Whereas, bathing occurred soon after delivery in Nigerian, but was delayed for several hours or until the next day for most Tanzanian and Ethiopian narrative mothers (Adejuyigbe, et al, 2015). Present study also showed the ritual of massage which is consistent with finding of the study which also emphasized the practice of oil massage before bath by mothers (Joseph, et al, 2013).…”
Section: Hygiene Practicessupporting
confidence: 88%
“…Based on the ndings, early bathing of newborn was a very common practice especially in Nigerian sites due to a deeprooted belief that delay to bath the newborn would result in body odour. Worst still, when asked about keeping the baby warm, respondents across the sites rarely mentioned the recommended thermal care practices (SSC), suggesting that these were not perceived as salient (48). Such norms can clearly be responsible for poor coverage of SSC in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Table 6 illustrates the included qualitative study characteristics: seven studies included for review were conducted in the UK, Pakistan, Nepal, Nigeria, Ethiopia, Zambia and Tanzania. Three studies were qualitative only (Adejuyigbe et al 2015;Sacks et al 2015;Lavender et al 2009); four were mixed-methods of which for three (Shamba et al 2014;Fikree et al 2005;Mullany et al 2005) only the qualitative component fulfilled the inclusion criteria, and for one (Furber et al 2012) both components were included in the review.…”
Section: Management Of Dry Skinmentioning
confidence: 99%
“…There was a similar lack of evidence of thematic analysis and link between the data and conclusions in Sacks et al (2015); however this study was graded as moderate quality due to acknowledging reflexivity, ethical consideration and clear sampling and data collection strategies. Adejuyigbe et al (2015) was also graded as moderate quality. This study was well designed and conducted, but there was no acknowledgement of reflexivity and the sample size was unclear.…”
Section: Qualitative Synthesismentioning
confidence: 99%
See 1 more Smart Citation